Degradation of the Stigma of Prison as a Criminal School Through Supervised Sentence as an Alternative to Imprisonment - Rohmat Rohmat; Milda Istiqomah; Nurini Aprilianda (Universitas Negeri Semarang, 2024)
With the development of penal theory, the retributive approach to punishment is increasingly seen as misaligned with the needs of society. As a result, there is a recognized need for legal provisions that reflect societal values and emphasize punishment goals that strengthen the community. Prison sentences often lead to issues such as overcrowded facilities and a failure to meet punishment goals. Additionally, many convicts tend to become recidivists after completing their sentences in correctional institutions, reinforcing the stigma of prisons as